2001
DOI: 10.1021/ma002130y
|View full text |Cite
|
Sign up to set email alerts
|

Miniemulsion Living Free Radical Polymerization by RAFT

Abstract: Various living mechanisms have been used in bulk polymerization to produce via free radical polymerization both controlled polymers, i.e., with low polydispersity, and block copolymers. The common drawback of all these processes is the very low polymerization rate which derives from the decreased concentration of propagating radicals. This problem can be overcome in principle by operating in emulsion polymerization, so as to take advantage of radical segregation to decrease terminations without significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
180
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(193 citation statements)
references
References 33 publications
11
180
1
1
Order By: Relevance
“…[9] Much research has shown that the success in RAFT emulsion polymerization depends strongly on the choice of RAFT agent and polymerization conditions. [9,[175][176][177][178][179][180][181][182][183] Most work has focussed on styrene polymerization, [9,176,177,183] although RAFT emulsion polymerizations of BA [178] and methcrylates [9,13] have also been reported. Use of cumyl dithiobenzoate 22 as RAFT agent in ab initio emulsion polymerization of styrene is not recommended.…”
Section: Raft In Heterogeneous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Much research has shown that the success in RAFT emulsion polymerization depends strongly on the choice of RAFT agent and polymerization conditions. [9,[175][176][177][178][179][180][181][182][183] Most work has focussed on styrene polymerization, [9,176,177,183] although RAFT emulsion polymerizations of BA [178] and methcrylates [9,13] have also been reported. Use of cumyl dithiobenzoate 22 as RAFT agent in ab initio emulsion polymerization of styrene is not recommended.…”
Section: Raft In Heterogeneous Mediamentioning
confidence: 99%
“…[9,68,82,102,[185][186][187][188][189][190][191][192][193][194][195] We showed that RAFT in miniemulsion can be used to produce polystyrene of narrow polydispersity in a batch process. [9] Some retardation is observed with dithiobenzoate RAFT agents.…”
Section: Raft In Heterogeneous Mediamentioning
confidence: 99%
“…This increases the reaction time compared to conventional free radical and ionic polymerization [63]. Radical segregation efect introduced by (mini)emulsion polymerization in heterogeneous system, on the other hand, reduced the reaction time and suppressed radical termination [64,65]. Combining emulsion polymerization with RAFT, PS-PnBA-PS triblock copolymers with different molecular weight and composition were prepared in shorter reaction time [66].…”
Section: Poly[2 5-bis[(n-hexogycarbonyl)]styrene] (Pmpcs) Is a Mesogmentioning
confidence: 99%
“…A Tabela 1 apresenta os estudos publicados até a presente data sobre a produção de polímeros que utilizaram a técnica RAFT em miniemulsão. Conforme revisado, a técnica de polimerização RAFT em miniemulsão já foi adaptada para os principais tipos de monômeros comerciais (como, por exemplo, estireno [28,34,35, , metacrilato de metila [35,54,68,[74][75][76][77][78][79][80] ), sistemas inversos [23,52,[81][82][83][84][85][86] e sistemas contínuos de polimerização [87][88][89] ). Além dos trabalhos citados na P(AM-co-AA) Inverso [83] P(NIPAM-b-PEO) Inverso [82] a Poliestireno (PSt), poli(metacrilato de metila) (PMMA), poli(buitl metacrilato (PnBMA), poli(hidroxietil metacrilato) (PEHMA), poli(butil acrilato) (PnBA), poli(acetato de vinila) (PVAc), Poliacrilamida (PAM), poli(ácido acrílico), poli(2-dimetilamino (metacrilato de etila)) (PDMAEMA), ácido metacrílico (MAA), acrilato de dodecafluoro heptil (DFHA), acrilamida (AM), ácido acrílico (AA), isopopil acrilamida (NIPAM), poli(óxido de etileno) (PEO).…”
Section: Polimerização Raft Em Miniemulsãounclassified